IDENTIFIKASI PENGEMBANGAN POTENSI WISATA KULINER DI DESA BUKIT PENINJAUAN II KABUPATEN SELUMA - karnadi karnadi; Aan Zulyanto (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
Tourism is one of the leading sectors of Bengkulu province development strategy through Visit Wonderful Bengkulu 2020. This study aimed to identify the potential of culinary tourism in the village of Bukit Peninjauan II. The identification process included the potential of the Tourism Center, identification of competitive culinary products, and its development strategy. Descriptive study was used in this study, where the identification of potential culinary tourism analyzed through FGD, interviews, questionnaires and SWOT analysis. This study identified that most of the Culinary Products dominated by snack such as Kerupuk Baso, Kripik atau Opak Ubi Kayu, Jajanan Pasar, Rempeyek, Rengginang and Kripik Tempe. This study also found that the Development of Culinary Tourism was very potential, because of the excellence in the location and culinary product aspect. In terms of location, It has a strategic location, easily accessible, smooth access and popular. The character of an open minded, friendly, creative and hard-working community are other supporting factors. Based on the food products produced, several competitive advantages identified include good food taste, cheaper price and better size. In general, the quality of food produced is good enough, but the variety of culinary is limited so it needs to be improved.